Atlantic Spanish vocabulary: Contribution from the corpus of dialectal lexicon - Cáceres-Lorenzo, Mª Teresa (Onomázein, 2015)
The analysis of the dialectic vocabulary common to Andalusia and the Canary Islands (Spain) reveals the regional concurrences of Atlantic Spanish. Previous studies have defined these concurrences generally but have not established quantitative connections between the Peninsular and American regional variations. This paper reviews these possible lexical connections using recently published synchronic regional dictionaries. A quantitative and qualitative approach is employed to analyse a collection of Canary-Andalusian words, with the objective of recognising the level of concurrence in the dialectic group. The results reveal three distinct representative networks: a) Canary-Andalusian and American; b) Canary-Andalusian and concurrences with the Western and Eastern Iberian Peninsula; and c) Canary-Andalusian and Northern peninsular and Castilian words. These results clearly demonstrate the process of basic interference and the behaviour of the diffusion of the dialectic lexicon.